Comparison of S. stercoralis Serology Performed on Dried Blood Spots and on Conventional Serum Samples - Formenti, Fabio; Buonfrate, Dora; Prandi, Rosanna; Marquez, Monica; Caicedo, Cintia; Rizzi, Eleonora; Guevara, Angel G.; Vicuña, Yosselin; Huerlo, Francisco R.; Perandin, Francesca; Bisoffi, Zeno; Anselmi, Mariella (Frontiers in Microbiology, 2016)
Background. Dried blood spots (DBS) are used for epidemiological surveys on infectious diseases in settings with limited resources. In fact, DBS can help to overcome logistic difficulties for the collection, transport and storage of biological specimens. Objective. To evaluate the accuracy of S. stercoralis serology performed on DBS. Methods. A survey was proposed to children attending a school in the village of Borbon, Ecuador, and to their parents/guardians. Each participant gave consent to the collection of both serum and DBS specimens. DBS absorbed on filter papers were analyzed with a commercially-available ELISA test for Strongyloides stercoralis antibodies, in parallel to the standard serology. The agreement between the two methods was assessed through the Cohen’s kappa coefficient. Results. The study sample was composed by 174 children and 61 adults, for a total of 235 serum and 235 DBS samples. The serology was positive in 31/235 (13%) serum samples, and in 27/235 (11%) DBS: 4 samples resulted discordant (positive at standard serology). Cohen’s kappa resulted 0.921 (95% CI 0.845 - 0.998), indicating a high rate of concordance. Conclusion. DBS are suitable for in field-surveys requiring serological testing for S. stercoralis.